2007
DOI: 10.2134/agronj2006.0135
|View full text |Cite
|
Sign up to set email alerts
|

By‐Plant Prediction of Corn Forage Biomass and Nitrogen Uptake at Various Growth Stages Using Remote Sensing and Plant Height

Abstract: As research intensifies on developing precision agricultural practices for corn (Zea mays L.) production, an important component will be to identify the scale at which these practices should be implemented. We hypothesized that optical sensing can be used to measure individual corn plant biomass and N uptake. A 3-yr study was conducted at three locations in Oklahoma. Optical sensor readings of normalized difference vegetation index (NDVI) and plant height measurements were collected on individual corn plants a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
116
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 16 publications
14
116
1
6
Order By: Relevance
“…Canopy temperature has been studied for decades as an indicator of stress [1] [2], to evaluate drought tolerance [3], and for scheduling irrigations [4]. Plant height is of interest due to its role in determining a variety of plant traits [5], and as an indicator of yield and biomass [6] [7] [8] [9]. Modern Instrumentation Modern mobile farm vehicles, such as tractors and sprayers, are being designed with more electronic features and have potential for interfacing sensors, enabling the collection of large amounts of data while working [10].…”
Section: Introductionmentioning
confidence: 99%
“…Canopy temperature has been studied for decades as an indicator of stress [1] [2], to evaluate drought tolerance [3], and for scheduling irrigations [4]. Plant height is of interest due to its role in determining a variety of plant traits [5], and as an indicator of yield and biomass [6] [7] [8] [9]. Modern Instrumentation Modern mobile farm vehicles, such as tractors and sprayers, are being designed with more electronic features and have potential for interfacing sensors, enabling the collection of large amounts of data while working [10].…”
Section: Introductionmentioning
confidence: 99%
“…Thenkabail et al (2000) found that the accuracy in estimating plant height could be improved by using reflectance in narrow spectral wavebands in the red and NIR regions (R 2 = 0.64). Freeman et al (2007) developed a 3-dimensional index based on the multiplication of NDVI and plant height to estimate corn biomass at early and later stages (R 2 = 0.66 and 0.45), yield (R 2 = 0.62 and 0.64), and N uptake (R 2 = 0.77 and 0.46). Liu and Wiatrak (2011) proposed the use of plant height, NDVI and LAI in estimating corn grain yield.…”
Section: Introductionmentioning
confidence: 99%
“…The irrigation provided during the experiment was similar on both years in order to provide similar management conditions and without influencing the outcome. Thus; both external factors (temperature and rainfall) influenced directly the development and production of the plants; because there are a positive relationships among plant height, forage yield, dry matter and fiber content (32)(33)(34) . For animal production, producers need to consider the sowing season in order to obtain an adequate forage yield and nutritional value aimed to increase the animal productivity (17,35,36) .…”
Section: Discussionmentioning
confidence: 99%